2020
DOI: 10.3390/antiox9020134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Induced by Oxidative Stress that Impair Human Sperm Motility

Abstract: A state of oxidative stress (OS) and the presence of reactive oxygen species (ROS) in the male reproductive tract are strongly correlated with infertility. While physiological levels of ROS are necessary for normal sperm functioning, elevated ROS production can overwhelm the cell’s limited antioxidant defenses leading to dysfunction and loss of fertilizing potential. Among the deleterious pleiotropic impacts arising from OS, sperm motility appears to be particularly vulnerable. Here, we present a mechanistic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 173 publications
(226 reference statements)
2
108
0
4
Order By: Relevance
“…Due to the greater degree of compaction of mammalian sperm DNA and limited DNA-damaging defense and repair systems, spermatozoa are highly sensitive to OS [ 22 ]. ROS-mediated spermatozoa DNA damage is a main reason for male infertility [ 23 ]. A previous study verified that hAMSCs demonstrated a powerful potential to ameliorate OS in BMMSCs induced by H 2 O 2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the greater degree of compaction of mammalian sperm DNA and limited DNA-damaging defense and repair systems, spermatozoa are highly sensitive to OS [ 22 ]. ROS-mediated spermatozoa DNA damage is a main reason for male infertility [ 23 ]. A previous study verified that hAMSCs demonstrated a powerful potential to ameliorate OS in BMMSCs induced by H 2 O 2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, chronic exposure to high levels of PM 10 , PM 2.5 and individual air pollutants such as NO 2 and sulfur dioxide (SO 2 ) are negatively associated with sperm count, motility and testicular volume in infertile subjects 52,53 . The mechanisms of spermatogenesis damage by environmental agents are largely unknown, although radical oxygen species (ROS) imbalance and associated oxidative stress may be the common denominator through which pollutants alter the most sensitive parameters of seminal quality such as sperm count, motility, morphology and integrity of sperm DNA [54][55][56] . As a matter of fact, sperm cells are highly sensitive to the pro-oxidant effects of environmental pollutants, due to the limited volume of the cytoplasmic space, with less antioxidant defence, and sperm membrane lipids are target of ROS 57 .…”
Section: Sperm Decline In Polluted Areasmentioning
confidence: 99%
“…This Special Issue on ROS and male fertility is composed of four original contributions that provide new data on the role of SOD [57] and PRDXs [58] as essential antioxidants in the epididymis, and PRDXs as novel players in the protection of gonocytes against oxidative stress [59] and the participation of glutathione-S transferase omega 2 in the regulation of sperm function during capacitation [60]. The Special Issue is completed with six review articles that provide an update on the molecular changes induced by oxidative stress that impairs human sperm motility [61], the importance of ROS in determining the functionality of spermatozoa and situations in which oxidative stress occurs and impacts on male fertility [24], the oxidation of the sperm nucleus and the impact of oxidative stress on the paternal genome [62], the importance of using appropriate tools to study the role of ROS in sperm and infertility [63], and an exhaustive evaluation of ROS production and its relevance in male fertility and antioxidant therapy [64]. The characterization of the redox regulation and effects of oxidative stress in equine spermatozoa is also included in this Special Issue [65].…”
mentioning
confidence: 99%